Capnocytophaga canimorsus Bloodstream Infection Associated with an Urticarial Exanthem - John C. Goetzinger; Austin L. LaGrow; Dena R. Shibib; Sharanjeet K. Thind (Case Reports in Infectious Diseases)
Background. Capnocytophaga canimorsus is a fastidious, slow-growing, Gram-negative rod that is a commensal bacterium in normal gingival flora of canine and feline species. Infection with the organism may cause disease ranging from flu-like symptoms to disseminated intravascular coagulation (DIC), fulminant sepsis, meningitis, and endocarditis with an overall fatality rate of 6–26%. Risk factors for infection from C. canimorsus include immunosuppression, alcoholism, and asplenia. Case Presentation. We describe an unusual case with a relatively indolent clinical course and an urticarial exanthem in an otherwise young immunocompetent patient with a history of type 1 diabetes. The patient presented to the Emergency Department (ED) with a <1-day history of rhinorrhea, fever, and dyspnea. He met sepsis criteria on initial presentation, but left against medical advice and returned to the ED the following day, with new arthralgias and a diffuse rash, multiple erythematous, tender macules scattered across his trunk and extremities, and tonsillar erythema. He had not taken the doses of the prescribed amoxicillin. Blood cultures two days later signaled positive for growth with the Gram stain showing a Gram-negative rod. Three 7-8 cm tender targetoid lesions with central clearing were identified on the patient’s back. The patient reported two nonengorged ticks crawling on his body a week prior and sustaining a dog bite to his ear three weeks before presentation. Ultimately, the organism was identified as C. canimorsus through MALDI-TOF mass spectrometry and additional biochemical testing. He was given appropriate antibiotics and improved clinically thereafter. Despite the patient’s bacteremia, he never progressed to fulminant sepsis and followed a mild clinical course with several unusual characteristics. C. canimorsus is an uncommon cause of illness in humans, but is an important pathogen to consider when evaluating a patient with a dog bite, known risk factors, and an urticarial exanthem as empiric treatment may prevent severe outcomes.